POC19 Anti-Hu paraneoplastic sensory neuronopathy with underlying squamous cell carcinoma of the lung. Issue 11 (22nd October 2010) - Gozzard, P; Soon, D; Vincent, A; Lang, B
Abstract : Type 1 anti-neuronal nuclear antibody (ANNA-1), also known as anti-Hu, recognises a family of RNA binding proteins, expressed in neuronal nuclei throughout the human neuraxis. Its presence usually reflects immunity against neuroendocrine tumours, in particular small-cell-lung cancer (SCLC). When present with neurological symptoms, anti-Hu is diagnostic of a paraneoplastic syndrome according to published criteria. A 72-year-old woman with a 39 pack-year smoking history developed a subacute sensory neuronopathy and weight loss attributed to a nonmetastatic chest neoplasm. High titres of anti-Hu antibodies were detected. Her chest mass was completely resected and found immunohistochemically to be homogenous squamous cell carcinoma. PET imaging has not revealed a second tumour to date. We demonstrated Hu antigen positivity on immunoblot of patient sera before and after surgery. Sections of the patient's tumour were incubated with sera at 1:20 dilution for 1 h. We demonstrated immunoreactivity in sera from the patient, and a Hu-positive patient with SCLC; this was specific to the large nuclei of the patient's squamous cell tumour, indicating tumour anti-Hu immunoreactivity. Control sera (from a patient with SCLC and a healthy control) did not show any staining. In rare cases the tumour giving rise to anti-Hu antibody associated sensory neuronopathy may be the result of squamous metaplasia. This should be borne in mind when initial tumour surveillance fails to detect SCLC.